Type 2 Diabetes Prescribing Habits Amongst Providers to an Underserved Population - Cynthia King; Atem Fontem; Benjamin King; Dave Gothard (University of Minnesota Libraries Publishing, 2019)
Introduction: Type 2 diabetes mellitus (T2DM) affected over 30 million individuals in the United States as of 2015. Due to the national diabetes guidelines recommending drug selection based on several patient specific factors and varying formulary restrictions, prescribers are often inundated when selecting treatment. Currently, limited evidence is available regarding the primary factors influencing prescribers' drug therapy selection. Objectives: The purpose of this study was to identify factors that influence providers during T2DM medication selection. Methods: The study was conducted with providers at a large, academic, safety net health system. All prescribers were sent an electronic, optional and anonymous survey. Prescribers treating T2DM in non-pregnant adult patients were the only prescribers assessed. Factors evaluated were: cost, A1c, comorbidities, adherence, weight, tolerability, patient limitations, and use of guidelines. Results: A total of 86 prescribers responded, yielding a response rate of 31%. The respondents included physicians (56.3%), nurse practitioners (21.8%), medical residents (18.4%), and fellows (3.4%); with the majority practicing in internal or family medicine (47.1%). The most frequently prescribed T2DM medications included: metformin (83.8%), insulin (78.1%), and sulfonylureas (64.8%). Cost and A1c elevation were two of the major factors influencing prescribing of metformin (94.1% and 81.2%), insulin (57.4% and 69.6%), and sulfonylureas (81.2% and 89.9%) respectively. Due to cost concerns, respondents reported rarely or never prescribing glucagon-like peptide-1 agonists (GLP-1RA) and sodium-glucose co-transporter-2 inhibitors (SGLT2i) despite recognizing benefits on diabetes related comorbidities.   Conclusion: Although current literature from the national guidelines encourages the use of GLP-1RA and SGLT2i as first-line options after metformin in T2DM, these classes of medications were not reported among the most commonly prescribed despite providers correctly identifying positive medication attributes such as cardio- and nephroprotection and weight loss. However, cost of these medications appears to outweigh the benefits when selecting medication therapy.   Article Type: Original Research